Care migration: The connectivity between care chains, care circulation and transnational social inequality. (July 2018) - Lutz, Helma
One of the features of the global commodification of care is the outsourcing of care work to migrants. The aim of this article is to investigate theoretical responses to the incorporation of migrant care workers in transnational care arrangements. After a description of the scope of migrant care labour and the global care economy, the article summarizes the challenges posed by this empirical phenomenon and asks to what extent care migrations on a global scale have common denominators. The author discusses three topical concepts dealing with the impact of care migration for migrant caregivers and for their significant others who stay behind. The first is the Global Care Chain Concept, with its particular importance for transnational parenting; the second is the Care Circulation Concept. In different ways, both of them shed light on the contradictory characteristics of care migration. I then argue that the third concept, the theory of Transnational Social Inequality, is a necessary addition. By focusing on migrant care workers' contradictory position, this concept aims at understanding the new features of asymmetrical resource distribution in their global manifestation. Taken together, these concepts are considered helpful tools to analyse the commonalities and differences of a large range of specific cases. Many examples used in this article are concerned with care migration in Europe.